Does High Stock Price Synchronicity Always Hurt Mutual Fund Industry? Sentiment Matters. Issue 1 (2nd January 2019) - Dong, Feng; Wilson, Son Dang
ABSTRACT: Investors have agreed that high synchronicity of stock returns adversely influences professional funds' profitability. However, different market conditions where high synchronicity exists may have different effects on this relationship. This study incorporates aggregate investor sentiment as a market condition in the equation to explore whether and when the negative association between synchronicity and fund performance holds. The authors use a sample of actively managed U.S. equity mutual funds from 2000 to 2014 and employ a portfolio of 11 passively managed funds as the benchmark to measure fund performance and fund management skill. They find empirical evidence that synchronicity negatively impacts mutual funds' profitability when the investor sentiment is low. This negative relationship disappears in high-sentiment periods. They also find that in both low- and high-sentiment states, fund managers with superior stock selection skill make more profits from high synchronicity than the average.